SLANG LANGUAGE IN SOCIAL MEDIA X (TWITTER) - Berta Hutauruk; Agatha; Olivia Manurung; Suryani Sinaga; Novia Aryani (Merwinspy Publisher, 2024)
This research project investigates the phenomenon of slang in the context of social media, specifically Twitter. This research aims to examine different forms of slang and understand how they function in the context of online communication. The authors use qualitative methods to investigate the linguistic features and expressions that makeup slang on Twitter. In addition, this study also investigates the functional aspects of slang, specifically how slang facilitates communication, identity construction, and community building on the Twitter platform. This research investigation highlights the diverse forms and functions of various slang in social media discourse by content analysis. This research figure out that Different forms of slang and understand how they function in the context of online communication.